Electrical Interference Problemson Commercial Fishing Vessels – A Review - Pankaj Kumar Sinha; Preetha Sharan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Canadian Coast Guard (CCG) provides Marine Communications centre (MCC) with financial assistance surveyed for Electromagnetic Compatibility and Electromagnetic Interference (EMC/EMI) correlated troubles on industrial based fishing vessels less than twenty metres. The electrical condition should be provided for the vessels and it is the goal of the survey. By performing "electrical noise" measurement method the necessary data was obtained. Several autopilot systems are susceptible to High Frequency Single Side Band (HF SSB) transmitters due to the absence of electrical noise suppression scheme. The main objective of the survey is to analyse the better electrical noise suppression method for fishing vessels.